Efektivitas Aplikasi Layanan Pak Danan Dalam Pelayanan Administrasi Di Pemerintah Desa Plintahan - Apriliana, Serly; Sukmana, Hendra (Universitas Muhammadiyah Mataram, 2025)
This study aims to describe and analyze the effectiveness of the Layanan Pak Danan Application in administrative services at the Plintahan Village Government. The research employed a descriptive qualitative method with observation, interviews, and documentation, and data analysis was conducted using the Miles and Huberman model. Informants included the Village Head, the Village Secretary as the application operator, and the Head of Services. The findings reveal that in terms of goal achievement, the application has accelerated services, simplified registration, and enhanced transparency and accountability, although several administrative services are not yet accommodated in the system and the application lacks a formal legal framework. In terms of integration, the application encouraged coordination through socialization, tiered signature mechanisms, and handling of duplicate registers, yet initial integration was uneven due to reliance on specific roles. In terms of adaptation, village officials demonstrated improved ability to learn the application independently, adjust services to regulatory changes, and implement technical innovations to meet community needs, although technical issues such as system errors, unstable internet, and power outages remain obstacles. Thus, the effectiveness of the Layanan Pak Danan Application can be categorized as effective, although not yet fully optimal, and still requires improvements in service coverage, regulatory aspects, and supporting infrastructure